A Home Energy Management Algorithm in a Smart House Integrated with Renewable Energy - Saha, A.; Kuzlu, M.; Khamphanchai, W.; Pipattanasomporn, M.; Rahman, S.; Elma, O.; Selamogullari, U. S.; Uzunoglu, M.; Yagcitekin, B. (IEEE, 2014)
Demand response applications within smart grid provide excellent opportunities for peak demand reduction through demand side load management. In the context of a smart grid, renewable energy resources are getting immensely popular as many homeowners are now opting for renewable energy systems at their residence. This paper presents a home energy management algorithm integrated with a renewable energy system within a smart house environment. A detailed simulation study has been conducted to investigate benefits of the approach. Then, it has been validated with real case studies conducted in the smart house located at Yildiz Technical University (YTU) in Istanbul, Turkey.
Keywords: Demand response; home energy management algorithm; renewable energy and real-world implementation; PREDICTION; SYSTEM; Energy & Fuels; Engineering